Value Creation in the Fast Fashion Supply Chain: Evidence from Brazilian Retailers - Domingos Valladares; Felipe Felhberg Hermann; Attila Elod Blezs Junior; Miguel Afonso Sellitto (International Journal of Supply Chain Management, 2019)
The purpose of this article is to analyze the process of value creation in Fast Fashion Supply Chains. The research method is the multiple case study. The research object is a sample of Brazilian companies formed by three anchor tenants and one consultancy with wide actuation in the local market. The analysis model includes competitive elements such as strategy, product development, logistics, and technology. The main contribution and novelty of the article are the business model employed by the three anchor tenants and the competitive objectives pursued by the FFSC. The most important competitive objective is the collaboration to capturing trends and quickly develop, produce, and deliver products to customers in physical stores or online.